Monopsony in the Low-Wage Labor Market? Evidence from Minimum Nurse Staffing Regulations - Matsudaira, Jordan D. (The Review of Economics and Statistics, 2014)
This paper provides direct evidence on the extent of monopsony power in the low-wage labor market by estimating the firm-level elasticity of labor supply for nurse aides in the long-term care (nursing home) industry. Using exogenous variation in hiring induced by the passage of a state minimum nurse staffing law, I find that facilities initially out of compliance with the new law did not have to raise their wage offers relative to their competitors in order to hire more nurses. While this is consistent with perfect competition in simple monopsony models of the labor market, I discuss how the results may be more ambiguous in more complicated models.